Silicon-based negative electrode material with cage-shaped structure, preparation method of silicon-based negative electrode material, solid-state battery and power-related equipment

By using silicon-based anode material with a cage structure in all-solid sulfide batteries, the problems of poor interface stability, severe volume effect and unstable SEI film in the battery are solved, and the higher cycling performance of the battery is achieved and energy density.

CN119400823AInactive Publication Date: 2025-02-07四川新能源汽车创新中心有限公司

Patent Information

Application Number
CN202411489242.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The silicon-based anode faces the problems of poor interfacial stability, severe volume effects and instability of SEI film in all-solid sulfide batteries, resulting in low battery cycle stability and energy density.

Method used

A silicon-based negative electrode material having a cage structure is used, which consists of silicon particles, a polymer cladding layer and a carbon cladding layer. The polymer cladding layer is cross-linked by siloxane units to form a cage structure, and the carbon cladding layer is coated on the polymer cladding layer by carbonization, enhancing the mechanical support and electrochemical properties of the material.

Benefits of technology

By constructing a cage structure, the structural damage caused by changes in silicon volume is effectively suppressed, the contact stability between the electrode and the solid electrolyte is enhanced, the interface impedance is reduced, and the circulation performance and energy density of all-solid sulfide batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119400823A_ABST
    Figure CN119400823A_ABST
Patent Text Reader

Abstract

The invention provides a silicon-based negative electrode material with a cage-shaped structure, a preparation method of the silicon-based negative electrode material, a solid-state battery and electric equipment, and relates to the field of batteries. The silicon-based negative electrode material with the cage-shaped structure comprises an inner core, a polymer coating layer and a carbon coating layer, the polymer coating layer coats the inner core, and the carbon coating layer coats the polymer coating layer; the core comprises silicon particles, the polymer coating layer comprises a polymer, the polymer comprises one or more repetitive units, the repetitive units comprise siloxane units, and the repetitive units are crosslinked to form a cage-shaped structure. According to the silicon-based negative electrode material with the cage-shaped structure provided by the invention, by constructing the cage-shaped structure coating the surfaces of the silicon particles, structural damage caused by silicon volume change can be effectively inhibited, the contact stability between an electrode and a solid electrolyte is enhanced, and the interface impedance is reduced, so that the cycle performance and the energy density of a solid-state battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of batteries, and in particular to a silicon-based negative electrode material with a cage structure and a preparation method thereof, a solid-state battery and electrical-related equipment. Background Art

[0002] With the growing global demand for clean energy technology, especially for driving applications such as electric vehicles, smart grids and portable electronic devices, the development of battery technology is particularly important. Among them, all-solid-state sulfide batteries (ASSSBs) are regarded as a strong competitor for the next generation of advanced battery technology due to their excellent safety, high energy density and long cycle life. Sulfide solid electrolytes make it possible to achieve high energy density and long life batteries due to their high ionic conductivity, wide electrochemical window and good compatibility with metallic lithium.

[0003] However, despite the many theoretical advantages of all-solid-state sulfide batteries, their practical application still faces a series of technical challenges, especially in the selection and design of negative electrode materials. Silicon-based negative electrodes are widely considered to be a key component for achieving the high energy density goal of all-solid-state sulfide batteries because of their theoretical specific capacity far higher than that of commercial graphite negative electrodes (about 10 times). However, the volume change of silicon during the charge and discharge process is as high as about 300%, which not only causes the destruction of the electrode structure and the shedding of active materials, but also triggers repeated reconstruction of the solid-electrolyte interphase (SEI), which not only significantly reduces the cycle stability of the battery, but also may cause increased interface impedance, excessive local current density and thermal management problems, which seriously hinders the practical application of all-solid-state sulfide batteries.

[0004] Specific problems faced by silicon-based negative electrodes in sulfide solid-state batteries include: poor interface stability and poor interface contact between silicon and sulfide electrolytes, which lead to high interface impedance and increased side reactions, affecting the battery's charge and discharge efficiency and cycle stability. Drastic volume effect: The huge volume change of silicon during the charge and discharge process can easily lead to electrode particle rupture, loose electrode structure, and even separation from the electrolyte, seriously affecting the battery's electrochemical performance and service life. Unstable SEI film: Silicon particles are prone to rupture and reconstruction during repeated charge and discharge, which not only consumes a large amount of lithium, but may also cause internal short circuits, affecting the safety of the battery.

[0005] In order to solve the above-mentioned problems in the application of silicon-based anodes in all-solid-state sulfide batteries, researchers have conducted a lot of research and explored various strategies to improve the electrochemical performance and cycle stability of silicon-based anodes, but they still face a series of technical challenges in practical applications. Summary of the invention

[0006] The purpose of this application is to provide a silicon-based negative electrode material with a cage structure and a preparation method thereof, a solid-state battery and electrical equipment to solve the above-mentioned problems.

[0007] To achieve the above objectives, this application adopts the following technical solutions:

[0008] A silicon-based negative electrode material with a cage-shaped structure, comprising a core, a polymer coating layer and a carbon coating layer;

[0009] The polymer coating layer covers the inner core, and the carbon coating layer covers the polymer coating layer;

[0010] The core includes silicon particles, the polymer coating layer includes a polymer, the polymer contains one or more repeating units, the repeating units include siloxane units, and the repeating units are cross-linked to form a cage structure.

[0011] Preferably, the raw material of the polymer includes polymer monomers, and the polymer monomers include one or more of γ-glycidyl ether silyl propyl sesquioxane, trans-cyclohexanediol isobutylated cage silsesquioxane, nano-silica dispersed epoxy cage silsesquioxane, octamethylsiloxy cage silsesquioxane, octagonal cage silsesquioxane and epoxy cyclohexyl isobutylated cage silsesquioxane.

[0012] Preferably, the repeating unit further comprises an organic unit, the raw material of the organic unit comprises a complexing organic substance, and the complexing organic substance comprises one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone.

[0013] Preferably, the raw material of the carbon coating layer includes a carbon material precursor;

[0014] Preferably, the carbon material precursor includes one or more of petroleum asphalt, biomass material and resin;

[0015] Preferably, the biomass material comprises one or more of corn cobs, bamboo and walnut shells, and the resin comprises phenolic resin compounds and / or epoxy resin compounds;

[0016] Preferably, the silicon particles have a particle size of 10-500 nm and a purity of not less than 99.9%.

[0017] The present application also provides a method for preparing the silicon-based negative electrode material having a cage-shaped structure, comprising:

[0018] Mixing raw materials including the silicon particles, polymer monomers, and initiators, and performing polymerization reaction to obtain a primary cage structure material;

[0019] The primary cage-shaped structure material, the carbon material precursor and the solvent are mixed to obtain a suspension, and then carbonization treatment is performed in an inert atmosphere to obtain the silicon-based negative electrode material with a cage-shaped structure.

[0020] Preferably, before mixing the primary cage structure material, the carbon material precursor and the solvent to obtain a suspension, the primary cage structure material is first heat-treated under an inert atmosphere, and then the heat-treated primary cage structure material is mixed with the carbon material precursor and the solvent;

[0021] Preferably, the heat treatment temperature is 500-1000°C, the heating rate is 2-10°C / min, and the holding time is 2-10h.

[0022] Preferably, the method for preparing the silicon-based negative electrode material having a cage structure satisfies one or more of the following conditions:

[0023] (1) The raw materials for the polymerization reaction further include a complexing organic substance, and the complexing organic substance includes one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone;

[0024] Preferably, the amount of the complexing organic matter is 2-10% of the total mass of the raw materials for the polymerization reaction;

[0025] (2) the raw materials for the polymerization reaction further include a catalyst, and the catalyst includes a Lewis acid;

[0026] Preferably, the Lewis acid comprises one or more of aluminum trichloride, boron trifluoride, sulfur trioxide and ferric bromide;

[0027] Preferably, the amount of the catalyst is 0.01-1% of the total mass of the raw materials for the polymerization reaction;

[0028] (3) The initiator includes one or more of potassium sulfate, ammonium persulfate, sodium persulfate, tert-butyl peroxide and azobisisobutyronitrile;

[0029] Preferably, the amount of the initiator is 0.1-2% of the total mass of the raw materials for the polymerization reaction;

[0030] (4) The mass ratio of the silicon particles to the polymer monomer is 1:(0.02-0.1);

[0031] (5) The temperature of the carbonization treatment is 600-1000° C. and the time is 3-15 hours;

[0032] (6) After the carbonization treatment, the material may be crushed, washed and dried.

[0033] Preferably, the silicon particles are pretreated before use, and the pretreatment includes: soaking the silicon particles with acid, then washing once, soaking with alkali, washing twice, and drying;

[0034] The pre-processing satisfies one or more of the following conditions:

[0035] (1) The acid includes one or more of hydrofluoric acid, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, carbonic acid, sulfurous acid, nitrous acid, acetic acid, citric acid, oxalic acid, formic acid, and malic acid;

[0036] Preferably, the acid is one or more of hydrofluoric acid, hydrochloric acid, and nitric acid;

[0037] (2) The drying temperature is 50-200°C.

[0038] The present application also provides a solid-state battery, the raw materials of which include the silicon-based negative electrode material with a cage-shaped structure.

[0039] The present application also provides an electrical device, including the solid-state battery.

[0040] Compared with the prior art, the beneficial effects of this application include:

[0041] The silicon-based negative electrode material with a cage structure provided by the present application can effectively suppress the structural damage caused by the volume change of silicon by constructing a cage structure with a siloxane unit coated on the surface of silicon particles, enhance the contact stability between the electrode and the solid electrolyte, and reduce the interface impedance, thereby significantly improving the cycle performance and energy density of the all-solid-state sulfide battery. Among them, the polymer monomer selects a specific raw material, which not only provides good mechanical support, but also optimizes the charge transfer path, reduces resistance, and helps to improve the overall electrochemical performance of the all-solid-state battery. In addition, the present application can further enhance the contact stability with the solid electrolyte by forming a uniformly distributed carbon coating on the surface of the silicon particles, reducing the impedance at the interface, and the carbon coating helps to further buffer the volume change of silicon during the lithiation / delithiation process, thereby making the silicon-based negative electrode material with a cage structure show better cycle stability in the all-solid-state sulfide battery.

[0042] The present application provides a method for preparing a silicon-based negative electrode material with a cage structure, which achieves coating of a cage-structured polymer on the inner shallow layer and surface of a silicon particle by a polymerization reaction, and then obtains a carbon coating layer by a carbonization reaction. The process is simple, and the obtained negative electrode material effectively solves the problems of poor interface stability, severe volume effect, and unstable SEI film.

[0043] The solid-state batteries and electrical equipment provided in this application have excellent electrical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0045] Figure 1 A schematic diagram of the theoretical structure of a silicon-based negative electrode material with a cage structure provided in this application;

[0046] Figure 2 This is a SEM photo of the silicon-based negative electrode material with a cage-shaped structure obtained in Example 1;

[0047] Figure 3 The cycle performance diagram of the half-cell assembled with the negative electrode materials prepared in Example 1 and Comparative Example 1 at the same charge and discharge rate. DETAILED DESCRIPTION

[0048] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:

[0049] A silicon-based negative electrode material with a cage-shaped structure, comprising a core, a polymer coating layer and a carbon coating layer;

[0050] The polymer coating layer covers the inner core, and the carbon coating layer covers the polymer coating layer;

[0051] The core includes silicon particles, the polymer coating layer includes a polymer, the polymer contains one or more repeating units, the repeating units include siloxane units, and the repeating units are cross-linked to form a cage structure.

[0052] In an optional embodiment, the raw material of the polymer includes polymer monomers, and the polymer monomers include one or more of γ-glycidyl ether silyl propyl sesquioxane, trans-cyclohexanediol isobutylated cage silsesquioxane, nano-silica dispersed epoxy cage silsesquioxane, octamethylsiloxy cage silsesquioxane, octagonal cage silsesquioxane and epoxy cyclohexyl isobutylated cage silsesquioxane.

[0053] The cage-type silicon structure itself has certain gaps and elasticity, which can accommodate the embedding and extraction of lithium ions to a greater extent, reduce volume changes, and further enhance the structural stability and cycle life of the negative electrode material. Through nano-level structural design, cage-type silicon forms cavities or cage structures in the shallow layer inside the silicon particles (referring to the shallow position caused by the uneven surface of the silicon particles) or on the surface. This structure can not only increase the specific surface area of ​​the silicon material and promote the rapid transmission of lithium ions, but also effectively alleviate the volume change of the silicon material during the charging and discharging process and reduce the risk of material rupture. The dual combination of the cage structure embedded in the shallow layer inside the silicon particles and linked to the surface not only solves the problem of volume change of silicon materials during lithium ion cycles, but also ensures the rate of lithium ion embedding inside the silicon particles through shallow embedding, solving the expansion and rate problems at the root.

[0054] In an optional embodiment, the repeating unit further comprises an organic unit, the raw material of the organic unit comprises a complexing organic substance, and the complexing organic substance comprises one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone.

[0055] With the use of organic matter, flexible segments are introduced into the polymer coating layer, which further improves a series of problems caused by the volume expansion of silicon; at the same time, with the addition of organic matter, the mechanical support of the polymer coating layer is better.

[0056] Specific:

[0057] 1. Introduction of flexible segments: Introducing flexible segments (such as polyethylene glycol, PEG) into the polymer coating, which are usually composed of rotatable single bonds, allows the molecular structure to bend and stretch freely in space. This flexibility allows the polymer network to deform with the silicon particles without breaking when the volume changes, thereby reducing stress concentration caused by volume expansion and avoiding damage to the surface of the silicon particles.

[0058] 2. Enhanced mechanical support: By selecting appropriate organic matter (such as γ-glycidyl ether oxysilyl propyl sesquioxane, GPOSS), these organic matter can undergo cross-linking reaction with the surface of silicon particles during heat treatment to form a three-dimensional network structure. This structure not only provides good mechanical support, but also optimizes the charge transfer path, reduces resistance, and helps improve the overall electrochemical performance of all-solid-state batteries.

[0059] 3. Stress buffering: The presence of flexible segments allows the polymer coating to play a spring-like role when the silicon volume changes, absorbing and dispersing stress, and preventing irreversible deformation or rupture of silicon particles during the lithiation / delithiation process. This stress buffering effect helps improve the cyclic stability of the material.

[0060] 4. Interface stability: The polymer coating layer increases the contact stability between the silicon-based negative electrode and the solid electrolyte by tightly bonding with the surface of the silicon particles, reduces the interface impedance, and thus improves the cycle performance of the battery.

[0061] In an optional embodiment, the raw material of the carbon coating layer includes a carbon material precursor;

[0062] In an optional embodiment, the carbon material precursor includes one or more of petroleum asphalt, biomass material and resin;

[0063] In an optional embodiment, the biomass material includes one or more of corn cobs, bamboo and walnut shells, and the resin includes phenolic resin compounds and / or epoxy resin compounds.

[0064] The above carbon material precursor is a hard carbon material precursor.

[0065] like Figure 1 As shown, the present application preferably provides a silicon-based negative electrode material having a cage-shaped structure and the outermost layer of which is a carbon material.

[0066] In an optional embodiment, the silicon particles have a particle size of 10-500 nm and a purity of not less than 99.9%.

[0067] Optionally, the particle size of the silicon particles may be 10 nm, 50 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm or any value between 10-500 nm.

[0068] The present application also provides a method for preparing the silicon-based negative electrode material having a cage-shaped structure, comprising:

[0069] Mixing raw materials including the silicon particles, polymer monomers, and initiators, and performing polymerization reaction to obtain a primary cage structure material;

[0070] The primary cage-structured material, the carbon material precursor and the solvent are mixed to obtain a suspension, and then carbonization treatment is performed in an inert atmosphere (nitrogen, argon, etc.) to obtain the silicon-based negative electrode material with a cage-structure.

[0071] In an optional embodiment, before mixing the primary cage structure material, the carbon material precursor and the solvent to obtain a suspension, the primary cage structure material is first heat-treated under an inert atmosphere, and then the heat-treated primary cage structure material is mixed with the carbon material precursor and the solvent;

[0072] The purpose of the heat treatment is to obtain a solidified cage-shaped structure material with a polymer coating layer by heat-treating the primary cage-shaped structure material.

[0073] In an optional embodiment, the heat treatment temperature is 500-1000° C., the heating rate is 2-10° C. / min, and the holding time is 2-10 h.

[0074] Optionally, the heat treatment temperature can be 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃ or any value between 500-1000℃, the heating rate can be 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, 10℃ / min or any value between 2-10℃ / min, and the holding time can be 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h or any value between 2-10h.

[0075] In an optional embodiment, the method for preparing a silicon-based negative electrode material having a cage structure satisfies one or more of the following conditions:

[0076] (1) The raw materials for the polymerization reaction further include a complexing organic substance, and the complexing organic substance includes one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone;

[0077] In an optional embodiment, the amount of the complexing organic matter is 2-10% of the total mass of the raw materials for the polymerization reaction;

[0078] Optionally, the amount of the complexing organic matter may be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any value between 2% and 10% of the total mass of the raw materials for the polymerization reaction;

[0079] (2) the raw materials for the polymerization reaction further include a catalyst, and the catalyst includes a Lewis acid;

[0080] In an optional embodiment, the Lewis acid includes one or more of aluminum chloride, boron trifluoride, sulfur trioxide and ferric bromide;

[0081] In an optional embodiment, the amount of the catalyst is 0.01-1% of the total mass of the raw materials for the polymerization reaction;

[0082] Optionally, the amount of the catalyst can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1% or any value between 0.01-1% of the total mass of the raw materials for the polymerization reaction;

[0083] (3) The initiator includes one or more of potassium sulfate, ammonium persulfate, sodium persulfate, tert-butyl peroxide and azobisisobutyronitrile;

[0084] In an optional embodiment, the amount of the initiator is 0.1-2% of the total mass of the raw materials for the polymerization reaction;

[0085] Optionally, the amount of the initiator can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value between 0.1-2% of the total mass of the raw materials for the polymerization reaction;

[0086] (4) The mass ratio of the silicon particles to the polymer monomer is 1:(0.02-0.1);

[0087] Optionally, the mass ratio of the silicon particles to the polymer monomer may be 1:0.02, 1:0.03, 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, 1:0.09, 1:0.1 or any value between 1:(0.02-0.1);

[0088] (5) The temperature of the carbonization treatment is 600-1000° C. and the time is 3-15 hours;

[0089] Optionally, the temperature of the carbonization treatment may be 600°C, 700°C, 800°C, 900°C, 1000°C or any value between 600-1000°C, and the time may be 3h, 5h, 10h, 15h or any value between 3-15h;

[0090] (6) After the carbonization treatment, the material is further crushed, washed with water, and dried (to remove impurities and unreacted materials).

[0091] The drying is preferably carried out under vacuum at a temperature of 60-120°C.

[0092] In an optional embodiment, the silicon particles are pretreated before use, and the pretreatment includes: soaking the silicon particles with acid, then washing once, soaking with alkali, washing twice, and drying;

[0093] The pre-processing satisfies one or more of the following conditions:

[0094] (1) The acid includes one or more of hydrofluoric acid, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, carbonic acid, sulfurous acid, nitrous acid, acetic acid, citric acid, oxalic acid, formic acid, and malic acid;

[0095] In an optional embodiment, the acid is one or more of hydrofluoric acid, hydrochloric acid, and nitric acid;

[0096] (2) The drying temperature is 50-200°C.

[0097] Optionally, the drying temperature may be 50°C, 100°C, 150°C, 200°C or any value between 50-200°C.

[0098] The present application also provides a solid-state battery, the raw materials of which include the silicon-based negative electrode material with a cage-shaped structure.

[0099] The present application also provides an electrical device, including the solid-state battery.

[0100] The solid-state battery referred to here can be, for example, an all-solid-state sulfide battery, or it can be a solid-state battery having other silicon-based negative electrode materials with a cage structure provided in the present application, such as a semi-solid-state battery.

[0101] Among them, it should be noted that sulfide all-solid-state batteries have more stringent requirements on electrode materials, requiring higher ionic conductivity, lower interface resistance and better structural stability. When considering the special requirements of sulfide all-solid-state batteries for electrode materials, the cage-type silicon structure shows more significant advantages in ionic conductivity, interface resistance and structural stability compared to the ultra-thin conformal coating of polymers directly formed on the surface of traditional silicon or tin-based materials.

[0102] Specific:

[0103] 1. Ionic conductivity: The cage-type silicon structure has a higher specific surface area and more internal channels, which can serve as a fast transmission path for lithium ions. The voids and pores within the cage-type structure can accommodate more electrolytes, thereby increasing the contact area between the electrolyte and the electrode material, which is beneficial to the rapid transmission of lithium ions. If a polymer ultra-thin coating (such as CN107403910B) is formed only on the surface of the silicon particles, although the polymer ultra-thin conformal coating can improve the flexibility and expansion adaptability of the material, it mainly exists as a protective layer and has limited direct effect on improving ionic conductivity. The coating may reduce the direct contact area between the electrode material and the electrolyte to a certain extent, thereby limiting the transmission rate of lithium ions.

[0104] 2. Interface resistance: The high specific surface area and complex internal channel structure of the cage-type silicon structure help to form more electrolyte-electrode interfaces, and the fast ion transport on these interfaces can reduce the interface resistance.

[0105] The presence of ordinary coatings may introduce new interfaces, such as the interface between the coating and the electrode material, the interface between the coating and the electrolyte, etc. These interfaces may become the source of resistance. If the coating and the electrode material are not tightly bonded or have defects, the interface resistance will increase.

[0106] 3. Structural stability: The internal voids and pores of the cage-type silicon structure can effectively alleviate the volume changes during the lithium ion insertion / deinsertion process, thereby improving the structural stability of the material.

[0107] Although the polymer ultra-thin conformal coating can reduce the fracture of the negative electrode material to a certain extent, its adaptability to volume changes is relatively limited. Under extreme charging and discharging conditions, traditional silicon or tin-based materials may still be severely deformed or cracked due to excessive volume changes, resulting in a decrease in battery performance.

[0108] In summary, due to its unique structural characteristics, the cage-type silicon structure can more effectively improve ionic conductivity, reduce interface resistance and enhance structural stability in sulfide all-solid-state batteries compared to the ultra-thin polymer conformal coating directly formed on the surface of traditional silicon or tin-based materials. These advantages make the cage-type silicon structure one of the most promising electrode materials in sulfide all-solid-state batteries.

[0109] In addition, the application of the silicon-based negative electrode material with a cage structure provided by the present application in solid-state batteries has higher safety, because the use of solid electrolytes avoids the potential safety hazards such as thermal runaway, leakage and short circuit caused by liquid electrolytes. This is also something that the silicon-based negative electrode materials in the prior art cannot guarantee.

[0110] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0111] Example 1

[0112] This embodiment provides a silicon-based negative electrode material with a cage-shaped structure, and the preparation method thereof is as follows:

[0113] Step 1: Silicon powder pretreatment Select silicon powder with a particle size of 50nm and a purity of 99.9% as the core material, put it into a mixed solution containing hydrofluoric acid and nitric acid, and soak it for 20 minutes to remove the oxide layer on the surface of the silicon powder. Then take out the silicon powder, rinse it with deionized water 3 times, and then put it into a solution containing sodium hydroxide and soak it for 10 minutes to remove the metal impurities on the surface of the silicon powder. Finally, take out the silicon powder, rinse it with deionized water 3 times, and dry it in a vacuum environment at 80℃ for 2 hours to obtain the pretreated silicon powder.

[0114] Step 2: Silicon material coating The pretreated silicon powder is added to a solution containing γ-glycidyl ether oxygen silyl propyl sesquioxane (GPOSS) and polyethylene glycol (PEG), wherein m(Si):m(GPOSS)=1:0.1, the concentration of PEG is 0.01mol / L, and the amount of PEG is 5% of the total mass of the raw materials for polymerization. Then, Lewis acid (trifluoromethanesulfonic acid) and potassium persulfate are added, wherein the concentration of Lewis acid is 0.05mol / L, and the amount of Lewis acid is 0.08% of the total mass of the raw materials for polymerization; the concentration of potassium persulfate is 0.01mol / L, and the amount of potassium persulfate is 0.7% of the total mass of the raw materials for polymerization. The mixed solution is stirred at 60°C for 24 hours to allow the POSS monomer to undergo polymerization, cross-linking or covalent bonding reaction on the surface of the silicon particles to form a primary cage structure.

[0115] Step 3: Heat treatment: The silicon particles coated with the primary cage structure are placed in a tubular furnace, and heated to 800° C. at a heating rate of 5° C. / min in an argon environment, and kept at this temperature for 2 hours to further solidify the cage structure and enhance its stability.

[0116] Step 4: Post-treatment: Take out the solidified silicon-based negative electrode material, put it into a solution containing hydrofluoric acid, and soak it for 10 minutes to remove the residue on the surface. Then take out the silicon-based negative electrode material, rinse it with deionized water 3 times, and dry it in a vacuum environment at 80°C for 2 hours. Then, the dried material is evenly dispersed in N-methylpyrrolidone to form a suspension, and then the hard carbon precursor (corn cob) is placed in the suspension and heat treated (carbonized) in an inert gas atmosphere at a temperature of 800°C for 8 hours to evenly wrap the particle surface of the material in step three;

[0117] Finally, the composite material is centrifugally washed in deionized water for multiple times to remove impurities and unreacted products, and then vacuum dried at 80° C. and ball-milled and sieved to obtain a silicon-based negative electrode material with a cage-shaped structure.

[0118] The above-mentioned silicon-based negative electrode material with a cage structure includes a core, a polymer coating layer and a carbon coating layer; the polymer coating layer coats the core, and the carbon coating layer coats the polymer coating layer; the core is a silicon particle, and the polymer coating layer includes a polymer obtained by polymerizing γ-glycidyloxysilylpropylsesquioxane and reacting with polyethylene glycol, and the repeating unit includes a siloxane unit and an organic unit, and the repeating unit forms a cage structure.

[0119] Figure 2 This is a SEM photograph of the silicon-based negative electrode material with a cage-shaped structure obtained in Example 1.

[0120] Example 2

[0121] Referring to Example 1, the difference is that m(Si):m(GPOSS)=1:0.02, and the concentration of PEG is 0.03 mol / L. Then, Lewis acid (boron trifluoride) and potassium persulfate are added, wherein the concentration of Lewis acid is 0.08 mol / L, and the concentration of potassium persulfate is 0.04 mol / L.

[0122] Example 3

[0123] Referring to Example 1, the difference is that m(Si):m(GPOSS)=1:0.04, and the concentration of PEG is 0.6 mol / L. Then, Lewis acid (ferric bromide) and potassium persulfate are added, wherein the concentration of Lewis acid is 0.1 mol / L, and the concentration of potassium persulfate is 0.65 mol / L.

[0124] Example 4

[0125] Refer to Example 1, except that the curing heat treatment temperature is 1000° C., the heating rate is 5° C. / min, and the holding time is 2 h.

[0126] Example 5

[0127] Refer to Example 1, except that polyethylene glycol is not added, and other parameters are the same.

[0128] Comparative Example 1

[0129] Silicon powder pretreatment Select silicon powder with a particle size of 50nm and a purity of 99.9% as the core material, put it into a mixed solution containing hydrofluoric acid and nitric acid, and soak it for 20 minutes to remove the oxide layer on the surface of the silicon powder. Then take out the silicon powder, rinse it with deionized water 3 times, and then put it into a solution containing sodium hydroxide and soak it for 10 minutes to remove the metal impurities on the surface of the silicon powder. Finally, take out the silicon powder, rinse it with deionized water 3 times, and dry it in a vacuum environment at 80°C for 2 hours to obtain the pretreated silicon powder. Step 2: Silicon material coating The pretreated silicon powder is added to a solution containing γ-glycidyl ether oxygen silyl propyl sesquioxane (GPOSS) and polyethylene glycol (PEG), wherein the concentration of POSS is 10mM and the concentration of PEG is 20mM. Next, add Lewis acid (such as trifluoromethanesulfonic acid) and potassium persulfate, wherein the concentration of Lewis acid is 1mM and the concentration of potassium persulfate is 2mM. The mixed solution is stirred at 60° C. for 24 hours to allow the POSS monomers to undergo polymerization, cross-linking or covalent bonding reactions on the surface of silicon particles to form a silicon-based negative electrode material.

[0130] Comparative Example 2

[0131] Silicon powder pretreatment: Select silicon powder with a particle size of 50nm and a purity of 99.9% as the core material, put it into a mixed solution containing hydrofluoric acid and nitric acid, and soak it for 20 minutes to remove the oxide layer on the surface of the silicon powder. Then take out the silicon powder, rinse it with deionized water 3 times, and then put it into a solution containing sodium hydroxide and soak it for 10 minutes to remove the metal impurities on the surface of the silicon powder. Finally, take out the silicon powder, rinse it with deionized water 3 times, and dry it in a vacuum environment at 80℃ for 2 hours to obtain the pretreated silicon powder for use as a silicon negative electrode.

[0132] Comparative Example 3

[0133] Silicon powder pretreatment: Silicon powder with a particle size of 50nm and a purity of 99.9% is selected as the core material, and it is placed in a mixed solution containing hydrofluoric acid and nitric acid and soaked for 20 minutes to remove the oxide layer on the surface of the silicon powder. Then the silicon powder is taken out, rinsed with deionized water 3 times, and then placed in a solution containing sodium hydroxide and soaked for 10 minutes to remove the metal impurities on the surface of the silicon powder. Finally, the silicon powder is taken out, rinsed with deionized water 3 times, and dried in a vacuum environment at 80°C for 2 hours to obtain pretreated silicon powder; then the dried material is evenly dispersed in N-methylpyrrolidone to form a suspension, and then the hard carbon precursor (corn cob) is placed in the suspension and heat-treated (carbonized) in an inert gas atmosphere at a temperature of 800°C to uniformly wrap it on the particle surface of the silicon material; finally, the above composite material is centrifuged and washed in deionized water for multiple times to remove impurities and unreacted products, and then vacuum dried at 80°C, and after ball milling and screening, a silicon-based negative electrode material is obtained.

[0134] Comparative Example 4

[0135] Refer to Example 1, except that no carbon coating layer is included, and other parameters are the same.

[0136] Comparative Example 5

[0137] Refer to Example 1, except that the carbon coating layer is soft carbon (polyacrylonitrile (PAN) fiber is used in step 4 instead of hard carbon precursor), and other parameters are the same.

[0138] Comparative Example 6

[0139] Refer to Example 1, except that the polymer coating does not undergo the heat treatment of step 3, and the other parameters are the same.

[0140] Electrical performance test: The materials of Example 14 and Comparative Sample 16 were used as active materials respectively, and the active materials were mixed with LiP6S5Cl, VGCF, and PVDF in a mass ratio of 60:38:2:2, and wet-coated on the surface of carbon-coated copper foil to obtain a negative electrode sheet, which was dried and cut to obtain a negative electrode sheet with a diameter of 10 mm. The negative electrode sheet was placed in a polyetheretherketone tube with a diameter of 10 mm, and then 80 mg of LiP6S5Cl was weighed and added to the polyetheretherketone tube. The tube was pressed and molded at a pressure of 20 MPa and tightly contacted with the negative electrode sheet. Finally, a piece of Li-In alloy was added to the other side of LiP6S5Cl, and pressed and molded at a pressure of 320 MPa to prepare a half-cell with a three-layer structure (negative electrode sheet / LiP6S5Cl / Li In alloy).

[0141] Test conditions: Charge and discharge tests were performed at 45°C with a rate of 0.05C and 0.5C and a cut-off voltage of 0.61 to 1.5V. Half cells were tested at a pressure of 20MPa. The internal pressure changes of lithium-ion batteries were tested online using an in-situ test device. The perturbation amplitude was 10mV in the frequency range of 0.1Hz to 100kHz, and the AC impedance spectrum of the battery was measured before the charge and discharge cycle.

[0142] Table 1 Test results

[0143]

[0144]

[0145] Figure 3 Cyclic performance diagram of half-cells assembled with negative electrode materials prepared in Example 1 and Comparative Example 1 at different charge and discharge rates.

[0146] From the above data and characterization, it can be clearly observed that the composite silicon negative electrode material obtained in Example 1 has a small volume expansion and excellent electrochemical performance, while the negative electrode materials obtained in Comparative Examples 1, 2 and 3 have poor electrochemical performance. Table 1 lists the test results of different embodiments and comparative examples on the first coulombic efficiency, 0.05C charging specific capacity, 0.5C cycle 200-week capacity retention rate, pressure change during in-situ pressure test charging and discharging, and charge transfer impedance. Through the analysis of these data, we can draw the following conclusions: The first coulombic efficiency of Examples 1 to 5 is higher than 80%, of which Example 1 is as high as 90%, showing good electrochemical activity. In contrast, the first coulombic efficiency of Comparative Examples 1 to 6 is low, especially Comparative Example 2 is only 65%, which may be due to the lack of an effective structural stabilization mechanism to resist the volume change of silicon particles during lithium ion insertion / deinsertion. Secondly, Example 1 shows the highest specific capacity of 1956mAh / g, which shows that the silicon-based negative electrode material has a higher theoretical capacity. Among the comparative examples, the specific capacity of comparative example 1 is the lowest, which is 1688mAh / g, indicating that the electrochemical performance of the material is not as good as those materials that have been specially treated. In addition, the capacity retention rate of Example 1 reaches 91%, indicating that the material can still maintain a high capacity after a long cycle. The capacity retention rates of comparative examples 1 to 3 dropped to 77%, 66% and 70%, respectively, indicating that they are not as good as the embodiment materials in terms of cycle stability. Further, the pressure change during the charge and discharge process was tested by in-situ pressure. The pressure change of Example 1 was the smallest, only 0.2MPa, which shows that its volume change during the charge and discharge process was well controlled. The pressure change of comparative example 1 was the largest, which was 4.1MPa, indicating that the material had a large volume change during the charge and discharge process, which may lead to structural instability. Accordingly, the charge transfer impedance of Example 1 was the lowest, which was 20Ω, which means that the material has a lower interface impedance, which is beneficial to improve the power density of the battery. The charge transfer impedances of comparative examples 1 to 3 were 40Ω, 80Ω and 65Ω, respectively, and higher impedance may affect the output performance of the battery.

[0147] In general, Examples 1 to 5 show better electrochemical performance than Comparative Examples 1 to 6, especially in terms of capacity retention, volume expansion control and interface impedance. These performance differences can be attributed to the design of the silicon-based negative electrode material with a cage structure, which helps to reduce the volume change of the silicon-based material during the charge and discharge process and improve the structural stability and electrochemical performance of the material.

[0148] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A silicon-based negative electrode material with a cage structure, characterized in that: comprising a core, a polymer coating layer and a carbon coating layer; The polymer coating layer covers the inner core, and the carbon coating layer covers the polymer coating layer; The core includes silicon particles, the polymer coating layer includes a polymer, the polymer contains one or more repeating units, the repeating units include siloxane units, and the repeating units are cross-linked to form a cage structure.

2. The silicon-based negative electrode material with a cage structure according to claim 1, characterized in that: The raw materials of the polymer include polymer monomers, and the polymer monomers include one or more of γ-glycidyl ether oxygen silyl propyl sesquioxane, trans-cyclohexanediol isobutylated cage silsesquioxane, nano-silica dispersed epoxy cage silsesquioxane, octamethylsiloxy cage silsesquioxane, octagonal cage silsesquioxane and epoxy cyclohexyl isobutylated cage silsesquioxane.

3. The silicon-based negative electrode material with a cage structure according to claim 1, characterized in that: The repeating unit further comprises an organic unit, the raw material of the organic unit comprises a coordinated organic substance, and the coordinated organic substance comprises one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone.

4. The silicon-based negative electrode material with a cage structure according to any one of claims 1 to 3, characterized in that: The raw material of the carbon coating layer includes a carbon material precursor; Preferably, the carbon material precursor includes one or more of petroleum asphalt, biomass material and resin; Preferably, the biomass material comprises one or more of corn cobs, bamboo and walnut shells, and the resin comprises phenolic resin compounds and / or epoxy resin compounds; Preferably, the silicon particles have a particle size of 10-500 nm and a purity of not less than 99.9%.

5. A method for preparing the silicon-based negative electrode material with a cage structure according to any one of claims 1 to 4, characterized in that: include: Mixing raw materials including the silicon particles, polymer monomers, and initiators, and performing polymerization reaction to obtain a primary cage structure material; The primary cage-shaped structure material, the carbon material precursor and the solvent are mixed to obtain a suspension, and then carbonization treatment is performed in an inert atmosphere to obtain the silicon-based negative electrode material with a cage-shaped structure.

6. The method for preparing a silicon-based negative electrode material having a cage structure according to claim 5, characterized in that: Before mixing the primary cage structure material, the carbon material precursor and the solvent to obtain a suspension, the primary cage structure material is first heat-treated under an inert atmosphere, and then the heat-treated primary cage structure material is mixed with the carbon material precursor and the solvent; Preferably, the heat treatment temperature is 500-1000°C, the heating rate is 2-10°C / min, and the holding time is 2-10h.

7. The method for preparing a silicon-based negative electrode material having a cage structure according to claim 5, characterized in that: One or more of the following conditions are met: (1) The raw materials for the polymerization reaction further include a complexing organic substance, and the complexing organic substance includes one or more of polyethylene glycol, polypropylene glycol, polyethylene glycol dimethyl ether, and polyvinyl pyrrolidone; Preferably, the amount of the complexing organic matter is 2-10% of the total mass of the raw materials for the polymerization reaction; (2) the raw materials for the polymerization reaction further include a catalyst, and the catalyst includes a Lewis acid; Preferably, the Lewis acid comprises one or more of aluminum trichloride, boron trifluoride, sulfur trioxide and ferric bromide; Preferably, the amount of the catalyst is 0.01-1% of the total mass of the raw materials for the polymerization reaction; (3) The initiator includes one or more of potassium sulfate, ammonium persulfate, sodium persulfate, tert-butyl peroxide and azobisisobutyronitrile; Preferably, the amount of the initiator is 0.1-2% of the total mass of the raw materials for the polymerization reaction; (4) The mass ratio of the silicon particles to the polymer monomer is 1:(0.02-0.1); (5) The temperature of the carbonization treatment is 600-1000° C. and the time is 3-15 hours; (6) After the carbonization treatment, the material may be crushed, washed and dried.

8. The method for preparing a silicon-based negative electrode material having a cage structure according to any one of claims 5 to 7, characterized in that: The silicon particles are pretreated before use, and the pretreatment includes: soaking the silicon particles with acid, then washing them once, soaking them with alkali, washing them twice, and drying them; The pre-processing satisfies one or more of the following conditions: (1) The acid includes one or more of hydrofluoric acid, nitric acid, hydrochloric acid, sulfuric acid, phosphoric acid, perchloric acid, carbonic acid, sulfurous acid, nitrous acid, acetic acid, citric acid, oxalic acid, formic acid, and malic acid; Preferably, the acid is one or more of hydrofluoric acid, hydrochloric acid, and nitric acid; (2) The drying temperature is 50-200°C.

9. A solid-state battery, characterized in that: The raw material includes the silicon-based negative electrode material with a cage structure as described in any one of claims 1 to 4.

10. An electrical equipment, characterized in that: Including the solid-state battery as described in claim 9.

Citation Information

Patent Citations

  • Polymerization process for forming ultrathin conformal polymer coatings on electrode materials

    CN107403910B

  • Double-layer coated silicon-based composite negative electrode material and preparation method thereof

    CN111048769A

  • Silicon-based negative electrode material and preparation method thereof, negative electrode plate and lithium ion battery

    CN116470036A

  • Preparation method of silicon-based negative electrode material, silicon-based negative electrode material, silicon-based negative electrode plate and battery

    CN118039830A

  • Silicon-carbon negative electrode material and preparation method and application thereof

    CN118156449A

Cited By

  • Carbon electrode material for polypyrrole modified bio-based fuel cell and preparation method of carbon electrode material

    CN120589733A